PEMBUATAN GAME “TEBAK GAMBAR HEWAN” UNTUK ANAK SD KELAS 3 BERBASIS ANDROID - Widayanto, Aprih; Pradana, Wahyu Nur Pradana (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Bina Sarana Informatika, 2023)
Abstracts - The goal to be achieved in this Final Project is to create an animal-themed educational game by guessing pictures as the main gameplay element that can be run on Smartphone media. This is motivated by the unavailability of all animals in the children's residence and the absence of an educational park or zoo in the children's neighborhood. By using games as a medium for learning animal names, the author will make the learning process to recognize animal names more interesting. There are many things to learn and need to know in the process of making this Guess the Picture: World of Animals game. The first of course is the selection of the type of animal and the animals in it, the next is to make the design concept, of course all the design concepts in this game will be adjusted to the goals and themes, then the next process is to create or search game assets based on the concepts that have been selected and make preparations into the program (software) that has been selected. Here the author uses a main software, namely Construct2 which is a game designer application that uses HTML5 as its programming language. Keywords: Game, Education, Animal, Construct2, HTML5